PENDAMPINGAN TPQ DENGAN OPTIMALISASI BACA TULIS AL-QUR’AN UNTUK MENCIPTAKAN GENERASI QUR’ANI - Cholifatul Azizah; Allifia Hariaji; Farih Alfaza; Asnal Mala; Eli Masnawati; Mirza Elmy Safira; Alfiatul Izzati Irawan; Shinta Maulidia Safitri; Masfufah; Yuliastutik; Nelud Daraajatul Aliyah (Abdi Jurnal Publikasi, 2024)
Islamic religious education has an essential role in shaping the character and morals of the younger generation, especially in the context of Indonesian society, which is predominantly Muslim. One important element of religious education is the teaching of the Koran, which is carried out at the Al-Qur'an Education Park (TPQ). However, the quality of teaching at TPQ often faces significant challenges, including low reading and writing skills of the Qur'an among students. TPQ in rural areas sometimes still experience difficulties in implementing the method (Rahmawati, 2018). This problem can be caused by several factors, including lack of resources, and limited study time. A more interactive and personal teaching approach will be able to improve Al-Qur'an reading skills (Zulkarnain, 2017). The program "TPQ Assistance by Optimizing Al-Qur'an Reading and Writing to Create a Quranic Generation" aims to achieve several main results. First, this program aims to improve the reading and writing ability of the Al-Qur'an of children at TPQ in the villages of Tambak Lekok, Tampung, and Jati Rejo. In this activity, the ABCD (Asset Based Communities Development) strategy or method is used, where this method is a community development approach that focuses on the strengths and assets that already exist in the community.